EFFECT OF ADDITION COCONUT PULP AND BANANA PEEL ON PRODUCTION BIOGAS FROM COW MANURE - Fairuz, Adam (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
Biogas is a renewable or alternative energy utilizing the decomposition process of awide range of organicwastes that generates methane gas (CH4). The purpose of this study is to evaluate the effect of the addition of coconut pulp and banana peels on biogas yield from cow dung. Parameters to be observed include: characteristics of substrates, degree of acidity (pH), temperature, biogas production and biogas yield, as well as the flame from biogas burning. This research is expected to produce an appropriate technology for treating waste of coconut pulp and banana peels into value added products and scientific information on the effect of the addition of coconut pulp and banana peels to biogas. The experiment design was a completely randomized design of six treatments,with consecutive composition of cowdung : banana peel : coconut pulp namely A50:40:10, B50:30:20, C 50:20:30, D 50:10:40, E 50:0:50, and F 50:50:0 with 3 replications. The data were analyzed by using ANOVA followed byDuncan test. The results showed that the additionof coconut pulp and reductionof banana peels in the biogas composition affected pH, C/N ratio, and biogas production, but had no effect on the temperature, and biogas yield. The increase in coconut pulp resulted in lower pH, the C/N ratio, and biogas production. Optimum condition is the treatment with composition of 50:50:0 without the addition of coconut pulp with a C/N ratio of 21,22 and pH of 5,5-6,5. Keywords: banana peel, biogas yield, coconut pulp, C/Nratio, renewable energy.